Desain Mobile Robot dengan Differential Steering untuk Penyemprot Nutrisi Tanaman Melon di Greenhouse - ardiansyah al farouq; Silvi Prastiwi Renanda Putri (Universitas Muhammadiyah Surakarta, 2023)
Maintenance of melon cultivation is still carried out conventionally even though melon plants require different nutrients in each phase of vegetative and generative development. For this reason, an automation system is needed that can help distribute nutrients and pH in each planter bag. In this study, the automation system is realized in the form of a line follower robot using a PID (Proportional Integral Derivative) control system. The PID control system is used to correct errors from measuring input variables so that the system output matches the set point value to produce the smallest possible error. Based on the results of the experiments conducted, the best PID control parameter results were obtained with a value of Kp = 10, Ki = 0.5, and Kd = 1, where these values can respond to the position of the mobile robot line follower so that it always detects the set point value and has the fastest time to reach the finish with a time of 30,450 ms.